FDG-Avid Erythema Nodosum Lesions of Behçet Disease Demonstrated on FDG PET/CT - (:unkn) unknown (Lippincott Williams and Wilkins, 2021)
Behçet disease is a rare multisystemic vasculitis that can affect all sizes and types of blood vessels. Recurrent painful erythematous nodular lesions called erythema nodosum are the most common skin lesions of Behçet disease. Herein, we present 18F-FDG PET/CT images of erythema nodosum lesions in a patient with Behçet disease. © Wolters Kluwer Health, Inc. All rights reserved.
Keywords: 18F-FDG PET/CT; Behçet disease; erythema nodosum